Using of S-(-)-2-hydroxymethyl-1,1-dimethylpyrrolidinium tetrafluoroborate as additive to the background electrolyte in capillary electrophoresis - Maier, Vítězslav; Horáková, Jana; Petr, Jan; Drahoňovský, Dušan; Ševčík, Juraj (Journal of chromatography. A, Including electrophoresis and other separation methods, 2006)
We synthesised and used new type of quaternary ammonium salt [S-(-)-2-hydroxymethyl-1,1-dimethylpyrrolidinium tetrafluoroborate] as effective additive to acidic background electrolytes. We used this quaternary ammonium salt as effective agent for capillary zone electrophoresis separation of model mixture of five tricyclic antidepressants (amitriptyline, nortriptyline, imipramine, desipramine and clomipramine) as model analytes. We observed that addition of S-(-)-2-hydroxymethyl-1,1-dimethylpyrrolidinium tetrafluoroborate ([HMDP](+) [BF(4)](-)) to acidic background electrolytes leads to suppression of magnitude of electroosmotic flow (EOF) and gradually change the direction of the EOF. Baseline separation of five TAs was achieved by using of 91.1 mmol L(-1) (20 gL(-1)) of [HMDP](+) [BF(4)](-) in 25 mmol L(-1) sodium phosphate pH 2.5, where electroosmotic mobility was -11.3 x 10(-9) m(2) V(-1) s(-1). We achieved baseline separation of five TAs with using of [HMDP](+) [BF(4)](-) as water solution too. We observed that [HMDP](+) [BF(4)](-) can be used as buffer additive, which offers relatively smaller anodic electroosmotic flow instead of cationic surfactants that are mostly used for genarating of anodic electroosmotic flow in capillary electrophoresis.
Keywords: antidepresiva tricyklická; Acetonitriles; elektrolyty; methanol; elektroforéza kapilární; beta-Cyclodextrins; Pyrrolidines; Borates; osmóza; Osmosis; pyrrolidiny; Methanol; boritany; Antidepressive Agents, Tricyclic; acetonitrily; beta-cyklodextriny; Financing, Organized; Electrophoresis, Capillary; financování organizované; Electrolytes